2016
DOI: 10.1094/cchem-10-15-0199-r
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and In Vitro Bioaccessibility of Selenium from Osborne Fractions of Selenium‐Rich Cereal Grains

Abstract: Cereal Chem. 93(4):339-343Cereal crops cultivated in the seleniferous belt of Punjab, India, were observed to hyperaccumulate a significantly high concentration of selenium (20-123 µg/g). Selenium concentration (µg/g) in storage proteins of wheat, maize, and rice, namely, albumin (401, 280, and 29, respectively), globulin (264, 192, and 242, respectively), glutelin (563, 359, and 178, respectively), and prolamin (629, 339, and 257, respectively) indicated variable selenium levels, with prolamin contributing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The whole wheat grains accumulate up to 122.9 ± 0.6 µg/g Se than maize (26.5 ± 0.2 µg/g) and rice (19.7 ± 0.2 µg/g). In the in-vitro gastrointestinal digestion studies, the intestinal accessibility of Se describes its potential bioavailability through dietary supplementation to the SeDef population (Dhanjal, Sharma, & Nagaraja, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The whole wheat grains accumulate up to 122.9 ± 0.6 µg/g Se than maize (26.5 ± 0.2 µg/g) and rice (19.7 ± 0.2 µg/g). In the in-vitro gastrointestinal digestion studies, the intestinal accessibility of Se describes its potential bioavailability through dietary supplementation to the SeDef population (Dhanjal, Sharma, & Nagaraja, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The colour intensity was measured with fluorescence spectrometer (Perkin Elmer LS-45) at emission spectrum of 520 nm corresponding to the amount of selenite present in the wheat extracts (SeW/NSeW). The emission spectrum of NIST certified Selenium ICP standard solution (SRM-1349) was used for Se quantification (Dhanjal, Sharma, & Nagaraja, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These indicate that prolamin and globulin also contribute to the tolerance to Se toxicity in rice owing to their high capacities for selenoamino acids. Dhanjal et al [ 34 ] found that prolamin and globulin contained larger amounts of Se than glutelin and albumin, and prolamin showed a high capacity for Se at the high Se concentration treatments in wheat, maize, and rice.…”
Section: Discussionmentioning
confidence: 99%